Can Capitalists Continue to Squeeze the Income Share of Employees? - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2020)
There is much debate over the distributive share of employees in national income – how to measure it, whether it goes up or down and, of course, why it matters. But something in this debate often seems amiss. Like many aggregates, the national income share of employees is a synthetic measure. It's made up of two largely unrelated entities – the relative number of employees in society and their relative individual income – and these two entities don't have to move in the same direction. Indeed, in the United States they have trended in opposite directions for almost a century. In this short research note, which focuses on the United States, we examine these opposite movements, explain why they are important and suggest that, if they continue, the United States will be much more conflictual and crisis prone in the future than it is today.
Keywords: P16; J3; 330; income distribution; national accounts; power